The Influence of Values and Motivation on Organizational Culture in MSME Actors, Paguyuban Sri Tanjung, Yogyakarta City - Nany Noor Kurniyati; Huda Surya (International Forum of Researchers and Lecturers, 2025)
This study aims to explore the influence of values and motivation on organizational culture in Paguyuban Sri Tanjung, Yogyakarta, a platform for more than 90 Small and Medium Enterprises (MSMEs). The research employs a descriptive design and quantitative methods, involving 90 respondents selected through non-probability sampling techniques. Primary data were collected using a questionnaire with a Likert scale. The results reveal that both values and motivation have a positive and significant impact on organizational culture, with P-values of 0.000 and 0.005, respectively. However, the influence of leadership on organizational culture was found to be insignificant, with a P-value of 0.260. These findings align with previous research that highlights the significant role of values and motivation in shaping a strong organizational culture. Furthermore, the study provides valuable insights into the dynamics of MSMEs in Yogyakarta, contributing to a better understanding of how organizational culture influences business performance. The research also suggests that improving the organizational culture within MSMEs, especially by focusing on values and motivation, can enhance their competitiveness and sustainability in a rapidly evolving market. The findings support the need for businesses to foster a positive organizational culture to ensure long-term growth and success, particularly in the context of small and medium-sized enterprises in developing regions.